Kinetic analysis of enzymatic esterification of fatty acids and ethanol - Borio, Daniel Oscar; Trubiano, G.C.; Perez, Guillermo Agustin; Errazu, Alberto Felipe
The esterification of oleic acid and ethanol with immobilised lipase in a solvent-free media is presented in this work. The reaction has been carried out at a laboratory scale in a stirred tank reactor operating batchwise. The evolution of oleic acid conversion to ester was determined by using two analysis techniques: measurement of the acid index and gas chromatography. The influence of the operating conditions on the equilibrium conversion and conversion-time profiles was analysed. The amount of enzyme, temperature, initial alcohol/oleic acid molar ratio and initial water content were considered. A kinetic model has been developed for the enzymatic esterification of oleic acid and ethanol catalysed by Candida Antartica immobilised lipase. Some kinetic models were considered and a second order reaction kinetic was selected. The parameter adjustment was carried out by using a computer program based on Marquardt algorithms. The results from the simulated experiments by using the proposed model showed a satisfactory agreement with the experimental data. Fil: Borio, Daniel Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina Fil: Trubiano, G.C. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina Fil: Perez, Guillermo Agustin. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina Fil: Borio, Daniel Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. ...